Imdād al-mushtāq ilā Ashraf al-aḵẖlāq : yaʻnī Shaiḵẖ al-ʻUlamā Qut̤b al-ʻĀlam Ḥaz̤rat Ḥājī Imdādullāh Fārūqī Cishtī ... ke ḥālāt va malfūẓāt - Thānvī, Ashraf ʻAlī (Maktabah-yi Burhān, 1981)
Life of Imdādullāh Thānvi, 1817-1899, Indian scholar on Islam; includes a detailed editorial introduction by Nis̲ār Aḥmad Fāruqī, b. 1934.